Kajian Peraturan Perundang-Undangan Tentang Iklan Obat dan Peran Serta Masyarakat dalam Pengawasannya - Supardi, Sudibyo (Jurnal Kefarmasian Indonesia, 2009)
The problem of study is the drugs advertising control in print media and broadcast media have been done, but many of them deviated from the legislation. The aims of study are to describe of the legislation articles related to the drug advertising and the community participation in drug advertising control. Method of study is analysis secondary data of legislation articles related to the drug advertising and public participation. The Study based on the laws, government regulations, health ministers regulations, local regulations until a decision letters. The data analysis based on understanding article by article of legislation about the drug advertising. The results show that : 1. The drug advertising must be objective, complete and not misleading which published after approved by health ministry, 2. The drug advertising control is undertaken by The National Agency of Drug and Food Control. The cooperation with various organizations should be done to decrease deviating drug advertising from the legislation, 3. The Community participation in the drug advertising monitoring is in the complaint form to The National Agency of Drug and Food Control or the non government organizations related to drug advertising. The drug cortsumers if harmed by drug advertising can protest through the approach of administration punishment, the civil law, and the criminal law.